2009
DOI: 10.1002/ccd.21780
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies on thermistor‐based intracoronary temperature measurements: Effect of pressure and flow

Abstract: Taken together these observations suggest that thermistor-based sensors are not suited for assessing thermal heterogeneity in the vascular wall and that the data obtained so far in patients with acute coronary syndromes might have been flawed by pressure (and flow) artifacts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Further, a recent study showed that variations in coronary pressure and blood flow alter the temperature measurements with a thermistor, and temperature elevations observed in previous studies may have been due to artifact. 60 This study raises the validity of the findings on all previous thermography studies.…”
Section: Thermographysupporting
confidence: 67%
“…Further, a recent study showed that variations in coronary pressure and blood flow alter the temperature measurements with a thermistor, and temperature elevations observed in previous studies may have been due to artifact. 60 This study raises the validity of the findings on all previous thermography studies.…”
Section: Thermographysupporting
confidence: 67%
“…Mean temperature difference measured in the culprit lesion was 0.02°±0.01°C, which was below the resolution of the thermistor and not significantly different from the baseline temperature difference of 0.00°±0.01°C. In a recent article, Cuisset et al [26], by using the same system, showed that when the sensor was advanced across the lesion, an increase in the temperature signal (average 0.059°±0.028°C) was uniformly observed in all patients. However, the increase in the temperature signal was proportional to the pressure drop across the stenosis [26].…”
Section: Human In Vivo Intracoronary Thermography Studiesmentioning
confidence: 96%
“…In a recent article, Cuisset et al [26], by using the same system, showed that when the sensor was advanced across the lesion, an increase in the temperature signal (average 0.059°±0.028°C) was uniformly observed in all patients. However, the increase in the temperature signal was proportional to the pressure drop across the stenosis [26]. This study suggested that thermistor-based sensors may not be suited for assessing in vivo coronary thermal heterogeneity.…”
Section: Human In Vivo Intracoronary Thermography Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…In the current study, the issue of pressure is also demonstrated only in low flow circumstances. It would be helpful if blood flow was kept normal and obtain temperature measurements during changes of pressure [1].The interpretation of the results of the study, however, can be performed by considering the following concerns. Initially, the authors attempt to explain the findings of other in vitro and in vivo experimental and clinical studies on atheromatic plaque temperature measurements, by blood temperature measurements in the mentioned model.…”
mentioning
confidence: 99%